Role of neutrophil-to-lymphocyte ratio as a prognostic marker for Guillain-Barre syndrome: a Cross-sectional study from a tertiary care Hospital - Rabia Iqbal; Qamar-un-Nisa; Wajid Jawaid; Sumera Rafat Umer; Rabiya Khan; Samiksha (Journal of University Medical & Dental College, 2025)
BACKGROUND AND OBJECTIVE: Guillain-Barre Syndrome (GBS) is an acute polyradiculoneuropathy with variable course and prognosis in different patients. Neutrophil-to-lymphocyte ratio (NLR) has shown promise in predicting prognosis in Guillain-Barre syndrome. The objective of this study was to determine the role of NLR as a marker of prognosis for Guillain-Barre Syndrome.METHODOLOGY : It was a prospective, cross-sectional study of GBS patients aged 15–70, conducted using non-probability consecutive sampling from 11th February to 10th September 2025 at the Neurology Department of Dr. Ruth K. M. Pfau Civil Hospital, Karachi. Patients were sub typed and treated with plasmapheresis. Baseline clinical data and inflammatory markers, including NLR, were collected. Treatment response was assessed using the Hughes Disability Score; poor prognosis was defined as an NLR >4.4 or non-response. SPSS version 26 was utilized for data analysis.RESULTS : The study included 80 GBS patients (mean age 38.86 ± 15.8 years), mostly males (73.8%). The mean NLR was 7.18 ± 13.95. Higher NLR values (>4.4) were associated with poor clinical outcomes, as measured by the Hughes Disability Score. NLR showed a sensitivity of 48.48% and specificity of 80.85% and a diagnostic accuracy of 69.09% for predicting poor response. Acute motor and sensory axonal neuropathy (AMSAN) showed the highest prognostic accuracy among all studied variants of GBS.CONCLUSION: NLR aids in early risk stratification and predicts clinical outcomes after therapeutic interventions. However, it should complement, rather than replace, comprehensive clinical evaluations.